Bahaya Radikalisme Beragama Pada Generasi Muda - Nurpratiwi, Suci; Hidayah, Faqih; Yanjani, Haura; Devitasari, Khalissa; Dewiarni, Puja (Indonesian Journal of Islamic Educational Review, 2024)
The young generation is a transitional period from childhood to adulthood, wherephysical development undergoes emotional changes that give rise to curiosity, self-confidence, and maturity. The young generation is also called the next generation of the nation. The future of the country is in the hands of the younger generation. The younger generation has the potential and interest in themselves that must be developed to gain identity. Therefore, the role of the current generation is very important to advance and prosper the nation in the future. At this time is a modern time, where all activities carried out are digital and thedevelopment of sophisticated technology. It cannot be denied that this can have a huge impact on the younger generation. The younger generation will be influenced from both positive and negative sides. The negative side can be seen from the field of religion, namely the erosion of religious values. If Islamic values are not applied in life, problems will arise such as the emergence of radicalism.Religious values greatly influence the current generation in their development. Ayoung person must instill Islamic character and ethics in himself. Islam provides teachings on knowledge, actions, morals, behavior that can build a religious attitude.